Playground or church? implications for public administration from Trinity Lutheran v. Comer - Candreva, Philip J. (2019)
The roots of public administration are in the fields of management, political science, and the law. The law is underrepresented in the literature and is not as well understood by nonlawyer practitioners, yet it increasingly enables, constrains, and prescribes government action. In 2017, the U.S. Supreme Court ruled on a case involving whether a government grant awarded on secular criteria must be provided to a qualified church. This article contributes to the field's understanding of the interplay of law and administration by examining the constitutional issues in the case and their implications for public administration. By considering how this dispute was framed and the ways in which the court approached its resolution, public officials can better understand the issues in similar cases; anticipate potential disputes; and (re)design policies that will serve their communities, remain within constitutional limits, and reduce the likelihood of litigation. - Reproduced.